Análise do processo de desenvolvimento municipal : estudo comparativo entre dez municípios do estado de Mato Grosso – 2011 - Silva, Millane Chaves da (2015)
The following dissertation has as its main goal identify the factors that positively contributed on the development process of Mato Grosso state’s municipalities and regions in the year of 2011. The importance in unveil elements that come from political-institutional, socioeconomic and environmental trajectories is given due the need to know and understand the reasons that defined the different municipal development processes that happened in the state. With that in mind, it was built the Multidimensional Municipal Development Index (IDMM) that sought to evaluate the development on the socioeconomic, political-institutional and environmental dimensions, having as basis the Human Development Index (IDHM). The research was conducted through raising, treatment and analysis of data, indexes and indicators concerning those dimensions. The bibliographic research aimed to identify the importance of the institutions and the historical context, and the path dependence power, as factors that explain the trajectory of Mato Grosso’s municipalities development. In that sense, in the light of the institutional theory, and with the support of indexes, this dissertation confirms the hypothesis that the existence of a favorable institutional environment presents itself as a factor that explains municipal development, and that the existence of strong institutions can create favorable conditions for development. It was also identified the importance of public planning on the state early colonization processes, whether it was on public or private scope, on promoting development, having, however, as an ally and basis the social capital that exists on society, and the cooperation, trust and capacity in associations. Ten municipalities were evaluated through the IDMM methodology, and the results on the three dimensions show that it is necessary to search for balance among the development dimensions, and to seek incorporating the local or endogenous development as an viable alternative for mitigating the enclaves and reducing the economic, social, environmental and institutional inequalities on Mato Grosso state’s municipalities.